From protein-protein interactions to immune modulation: Therapeutic prospects of targeting Neuropilin-1 in high-grade glioma - Smith, Gregory T.; Radin, Daniel P.; Tsirka, Stella E. (Frontiers in Immunology, 2022)
In the past several years there has been a marked increase in our understanding of the pathophysiological hallmarks of glioblastoma development and progression, with specific respect to the contribution of the glioma tumor microenvironment to the rapid progression and treatment resistance of high-grade gliomas. Despite these strides, standard of care therapy still only targets rapidly dividing tumor cells in the glioma, and does little to curb the pro-tumorigenic functions of non-cancerous cells entrenched in the glioma microenvironment. This tumor promoting environment as well as the heterogeneity of high-grade gliomas contribute to the poor prognosis of this malignancy. The interaction of non-malignant cells in the microenvironment with the tumor cells accentuate phenotypes such as rapid proliferation or immunosuppression, so therapeutically modulating one target expressed on one cell type may be insufficient to restrain these rapidly developing neoplasias. With this in mind, identifying a target expressed on multiple cell types and understanding how it governs tumor-promoting functions in each cell type may have great utility in better managing this disease. Herein, we review the physiology and pathological effects of Neuropilin-1, a transmembrane co-receptor which mediates signal transduction pathways when associated with multiple other receptors. We discuss its effects on the properties of endothelial cells and on immune cell types within gliomas including glioma-associated macrophages, microglia, cytotoxic T cells and T regulatory cells. We also consider its effects when elaborated on the surface of tumor cells with respect to proliferation, stemness and treatment resistance, and review attempts to target Neuroplin-1 in the clinical setting.